Causal insights into GPS precision variability: an investigation into the ionospheric impact on GPS measurements throughout the solar cycle - Saracoglu, A. (Ist Nazionale Di Oceanografia E Di Geofisica, 2024)
This research paper investigates the influence of solar activity on GPS measurement accuracy, and, more specifically, its interaction with the ionosphere. The study spanned from 2002 to 2018, coinciding with the 11-year solar cycle. The focus was to assess the effects of solar activity on GPS time series: north, east, and vertical components. Monthly throughout this period, three-day GPS campaign data, encompassing the solar cycle, were collected. Using a global network of 40 GPS stations from the International GNSS Service, the study categorised stations into six regions based on climate zones, so as to address regional differences. Data were further segmented into 8-and 12-hour periods, thus creating new data sets to examine variability in measurement accuracy. The Precise Point Positioning module of the GIPSY-OASIS software (developed by NASA's Jet Propulsion Laboratory) was employed to analyse the data. The research also explored the relationship between solar activity, quantified by the number of sunspots, and the correlation between the phase ambiguity resolution ratio and standard error of GPS coordinate components. The results highlighted a significant inverse correlation between solar activity and GPS signals, ranging from moderately strong (-0.50) to relatively strong (-0.80), hence implying that greater solar activity corresponds to lower GPS accuracy. This phenomenon results from ionospheric effects on signal propagation, which induce errors such as delays and phase fluctuations in GPS signals.
Keywords: GPS; PPP; positioning accuracy; ionosphere; solar activity.